Pengaruh HRM Keadilan Organisasi, Manajemen Konflik, Etika Organisasi Terhadap Hubungan Karyawan dengan Intervening Iklim Kepercayaan - Winda Amelia; Dihin Septyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the modern corporate environment, organizational justice, effective conflict management, and strong ethics are crucial elements in creating harmonious and productive employee relationships. The purpose of this research is to find out how HRM influences organizational justice, conflict management, organizational ethics on employee relations with the intervening climate of trust. This research was conducted at the XYZ company which operates in the shoe manufacturing sector located in Pasar Kemis Tangerang. Descriptive – correlative research design with quantitative methods and using purposive sampling techniques which were distributed via (google form) to 275 respondents aged 18 – 60 years who worked in the production section of the company. Primary data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The conceptual model was analyzed using Structural Equation Modeling. The findings of this research reveal that organizational justice has a positive influence on employee relationships, management has a positive influence on employee relationships, organizational ethics has a positive influence on employee relationships, organizational justice has a positive influence on the climate of trust, conflict management has a positive influence on the climate of trust. , organizational ethics has a positive influence on the climate of trust, climate of trust has a positive influence on employee relations, climate of trust mediates the relationship between organizational justice and employee relations, climate of trust does not mediate the relationship between conflict management on employee relations and climate of trust does not mediate the relationship between organizational ethics on employee relations.